2006
DOI: 10.1103/physreve.73.046308
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and thermodynamics of axisymmetric flows: Theory

Abstract: We develop new variational principles to study the structure and the stability of equilibrium states of axisymmetric flows. We show that the axisymmetric Euler equations for inviscid flows admit an infinite number of steady state solutions. We find their general form and provide analytical solutions in some special cases. The system can be trapped in one of these steady states as a result of an inviscid violent relaxation. We show that the stable steady states maximize a (nonuniversal) H-function while conserv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
98
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(101 citation statements)
references
References 39 publications
3
98
0
Order By: Relevance
“…Furthermore, r −1 ∂ r r −1 ∂ r ψ + r −2 ∂ 2 z ψ = −ξ. In the inviscid, force-free limit, the global quantities conserved by the Euler equation are the energy E, the generalized helicities H f and the Casimirs I g , given by [7]: …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, r −1 ∂ r r −1 ∂ r ψ + r −2 ∂ 2 z ψ = −ξ. In the inviscid, force-free limit, the global quantities conserved by the Euler equation are the energy E, the generalized helicities H f and the Casimirs I g , given by [7]: …”
mentioning
confidence: 99%
“…Advances in that direction have been recently made for flows with symmetries (2D [6], axisymmetric [7]) using tools developed independently by Robert and Sommeria and Miller [8]. They consider freely evolving flows described by the Euler equation (no forcing and no dissipation).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Monchaux et al [22] investigated the properties of the mean and most probable velocity fields in the same configuration. They showed that these two fields are described by two families of functions [23] depending on both the viscosity and the forcing. For large values of the Reynolds number, in some regions, the flow behaves like a Beltrami flow in which vorticity is locally aligned with velocity.…”
Section: Introductionmentioning
confidence: 99%